2009
DOI: 10.1177/0027950109103691
|View full text |Cite
|
Sign up to set email alerts
|

Using Foundation Stage Profile Assessments To Assess Outcomes From Early Years Education

Abstract: In the past decade early years education has expanded throughout England with progressive extensions in entitlement to some hours of free provision. Furthermore, there is consistent evidence that shows that early years education leads to improvement in cognitive and social development for children. This paper uses the latest data from the Millennium Cohort Study to consider whether, in an era of near universal provision, receipt of early years education still leads to better outcomes for children than for thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…For example, the Millennium Cohort Study (MCS), a birth cohort study of children born across the UK in 2000-2001, has been useful in examining, amongst other things, the quality of childcare settings (Melhuish et al 2010), the establishment of Action for Children Children's Centres (Blewett et al 2011), the influence of different forms of early childcare (Hansen and Hawkes 2009), the levels of attendance in early years' education on assessments in the EYFS Profile at the end of Reception class (Hopkin, Stokes, and Wilkinson 2009) and results at Key Stage 1 (George, Stokes, and Wilkinson 2012). However, what very few of these studies have been able to do is to examine the impact of a major national educational policy in early years education.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Millennium Cohort Study (MCS), a birth cohort study of children born across the UK in 2000-2001, has been useful in examining, amongst other things, the quality of childcare settings (Melhuish et al 2010), the establishment of Action for Children Children's Centres (Blewett et al 2011), the influence of different forms of early childcare (Hansen and Hawkes 2009), the levels of attendance in early years' education on assessments in the EYFS Profile at the end of Reception class (Hopkin, Stokes, and Wilkinson 2009) and results at Key Stage 1 (George, Stokes, and Wilkinson 2012). However, what very few of these studies have been able to do is to examine the impact of a major national educational policy in early years education.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller sub-study of the MCS (Mathers et al, 2007) of around 300 early education settings and roughly 600 children, does include the same ECERS quality indicators that were available in the EPPE study. Analysis of these data (Hopkin et al, 2010) found no association between attendance at a high quality early education setting and FSP scores, but did show an association between high quality early education and other cognitive outcomes, measured by the naming vocabulary assessment from the British Ability Scales. 4 Unfortunately, the MCS sub-study only has information on KS1 attainment for a little over 400 cohort members, so is not suitable for our analysis.…”
Section: Introductionmentioning
confidence: 80%
“…Although the naming vocabulary assessment captures a limited aspect of child development at age three, whilst the KS1 assessment is a broader measure at age seven, we believe the comparison is valid. Hopkin et al (2009 and found that the naming vocabulary indicator was a strong predictor of a broad measure of child development at age five as measured by the FSP. In order to compare the naming vocabulary and KS1 measures, we use weighted data to convert them both into z scores with mean 0 and standard deviation of 1.…”
Section: Descriptive Statisticsmentioning
confidence: 95%
See 1 more Smart Citation